Low carrier recombination in polysiloxane gel electrolyte for high-performance DSSC. (1st April 2023) - Usman, Ida; Arsyad, Waode Sukmawati; Herman, Herman; Hidayat, Rahmat
Abstract: Previous research on quasi-solid-state DSSC (QSS-DSSC) that utilized polysiloxane-based polymer gel electrolytes (PGE) showed that the functional performance of the cells was highly affected by electrolyte infiltration into the TiO2 nano-porous layers. This study evaluated the efficiency enhancement in siloxane-based cells by introducing a TiCl4 pre-treatment process twice. We compared the impedance spectrum of PGE-based DSSC without (type-1 PGE) and with (type-2 PGE) with the addition of propylene carbonate, measured under dark and light illumination. The impedance spectra of both cells showed different characteristics at different condition measurements, especially in the high-frequency region. Unlike the type-2 PGE-based DSSC, the type-1 PGE-based DSSC did not show the transmission line characteristic, which indicated less charge carrier diffusion inside the TiO2 nano-porous layer. Under light illumination, the interfacial charge transfer between electrons inside TiO2 layers with the electrolyte (Rct ), and the electron lifetime inside TiO2 layers before it is recombined ( τ r ), became smaller for type-2 PGE-based DSSC and larger for type-1 PGE-based DSSC. This indicated that the recombination rate increased as the PGE became more vicious. This result supports the photovoltaic characteristics that yield current density and efficiency values of 16 mA cm −2 and 5.37% for type-2 PGE-based DSSC, 13.4 mA cm −2, and 4.72% for type-1 PGE-based DSSC. The challenge for further improvement in DSSC that employs PGE is to elevate the wetting capability of the gel inside the TiO2 layer without additional solvent since additional solvent eventually can reduce ionic concentration and consequently increase the Rct value as shown in the analysis of the impedance spectrum of TiO2 layer without dye.